(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In every health service facility in a hospital, it is obligatory to make medical records made by doctors and health workers related to the services provided by doctors and other health workers. Medical records made, both outpatient medical records and inpatient medical records, are stored in a medical record file storage area (filling).. Phe management of medical records with the standard Medical Record Information Management (MIRM) is to support orderly administration in the context of efforts to improve health services in hospitals which are supported by a medical record management system that is fast, precise, valuable, accountable, and focuses on patients and safety patients in an integrated manner. The purpose of this system plan is to make it easier for management and leaders to get a visual summary of information for decision making.